Apache - Landman, Tanya (London : Walker Books, 2007)
Fourteen-year-old Siki vows revenge on the Mexican raiders who brutally murdered her little brother, and turns away from the tradition roles women in her tribe fill to become an Apache warrior.
Young Adult.
Young Adult
Keywords: Apache Indians -- Juvenile fiction; Apache women -- Juvenile fiction; Revenge -- Juvenile fiction; Apache Indians -- Fiction; Apache women -- Fiction; Revenge -- Fiction; Apache Indians -- Fiction; Native American women -- Fiction; Revenge -- Fiction